The Change of Fat, Protein, Starch Contens and Electric Conductivity within Gaharu (Aquillaria malaccensis) Seeds - Dida Syamsuwida; Aam Aminah (Jurnal Manajemen Hutan Tropika, 2007)
One of the symptomps of seed ageing is broad changes of biochemical content within seeds which is causing the decrease of decrease viability, eventually. The aim of the study was to determine the change of Aquillaria malaccensis seeds biochemically during storage and desiccating. There were two trial in this study: 1) decreasing seed moisture content by desiccations for 6, 12, 18, 24, and 48 hours and 2) storing the seeds conventionally in two different condtions of storage (ambient room and air conditioner room). Since the moisture content of fresh seed on acceptance was low (15,9%) due to the delaying during transportation, reducing moisture content of the seed brought about the decrease of germination capacity down to zero. The content of protein, fat and starch of the seeds during desiccation and storage were mostly  changes which were indicating the deterioration of the seeds. The content of fat of fresh seeds was high (46,2%) and tended to remain high during desiccating. Meanwhile, the content of protein tended to increase and starch was decreased following desiccation. The content of fat and protein tended to increase and starch was decreased following desiccation. the content of fat and protein during storage weree reduced, while starch was increased for 8 weeks and then went down for the rest of storage. The electricconductivity within the seeds in both treatments (desiccation and storage) was increased which were indicating the leakage of membrane cells occured . Based on biochemical content changes, seed of Aquillaria malaccensiscould be categorized as recalcitrant type. However, to make the results more accurate it should be proved specifically by testing the physiological of seeds, simultaneously.Keywords : Aquillaria malaccensis, desiccations, fat, moisture content, protein